Boon or bane? Others' unemployment, well-being and job insecurity - Andrew E. Clark; Andreas Knabe; Steffen Rätzel (Institute for the Study of Labor (IZA), 2009)
The social norm of unemployment suggests that aggregate unemployment reduces the well-being of the employed, but has a far smaller effect on the unemployed. We use German panel data to reproduce this standard result, but then suggest that the appropriate distinction may not be between employment and unemployment, but rather between higher and lower levels of labour-market security, at least for men. Men with good job prospects, both employed and unemployed, are strongly negatively affected by regional unemployment. However, insecure employed men and poor-prospect unemployed men are less negatively, or even positively, affected. There is however no clear relationship for women. We analyse labour-market inequality and unemployment hysteresis in the light of our results.
urn:nbn:de:101:1-2009061958
Keywords: I31; D84; J60; 330; Unemployment; externalities; job insecurity; well-being; Arbeitslosigkeit; Regionaler Arbeitsmarkt; Arbeitsplatzsicherung; Sozialpsychologie; Lebenszufriedenheit; Deutschland